1986
DOI: 10.1152/jappl.1986.61.5.1667
|View full text |Cite
|
Sign up to set email alerts
|

Airway effects of purine nucleosides and nucleotides and release with bronchial provocation in asthma

Abstract: Adenosine, AMP, and ADP all caused similar concentration-related bronchoconstriction when inhaled by patients with asthma, whereas the adenosine hydrolysis product inosine had no effect. Geometric mean provocation concentrations of adenosine AMP and ADP causing a 20% fall in forced expiratory volume in 1 s (PCf20) were 2.34, 4.27, and 2.19 mumol/ml and 40% fall in specific airway conductance (PCs40) 3.16, 5.01, and 2.0 mumol/ml. Bronchoconstriction was rapid in onset, reaching a maximum 2-5 min after a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(95 citation statements)
references
References 0 publications
4
90
0
1
Order By: Relevance
“…Although only an association was shown between adenosine and airway obstruction, not a direct causal relationship, previous studies have suggested that whatever is the source of adenosine in the airways, an increase in its level would potentiate the airway obstruction produced by other bronchoconstrictor stimuli [28,29].…”
Section: Discussionmentioning
confidence: 95%
“…Although only an association was shown between adenosine and airway obstruction, not a direct causal relationship, previous studies have suggested that whatever is the source of adenosine in the airways, an increase in its level would potentiate the airway obstruction produced by other bronchoconstrictor stimuli [28,29].…”
Section: Discussionmentioning
confidence: 95%
“…Adenosine has long been thought to play a role in the pathogenesis of allergic airway disease and asthma (9,13,30,45). However, the mechanisms of adenosinemediated lung damage are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways are activated by extracellular purines, which include adenosine triphosphate (ATP) and its metabolites adenosine diphosphate, adenosine monophosphate (AMP), and adenosine. Adenosine, in particular, has been linked to infl ammatory airways diseases, 1 including twofold to fourfold elevations in blood 2,3 and BAL fl uid 4 of subjects with asthma. Similarly, adenosine concentrations in exhaled breath condensate (EBC) are elevated in subjects with stable asthma, 5,6 increased with asthma exacerbations, 7 and decreased with successful treatment.…”
Section: Original Research Obstructive Lung Diseasesmentioning
confidence: 99%